A Critical Examination of The Legal Protection Available to Those Who Hold Land Rights - Basri; Tamaulina Br. Sembiring; Ning Adiasih; Loso Judijanto; Endah Rantau Itasari (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The objective of this research is to analyse the legal protection of holders of land rights in development. The research employs a normative legal research method, utilising data sourced from literature studies, including laws and regulations on mining, as well as literature, such as books related to the subject matter. First, it is the duty of the State to protect holders of land rights certificates due to the aforementioned individuals' good faith and the state's decision to issue certificates as proof of land titles. Such certificates should not be canceled by the state without compensation. In light of this, it is essential to have valid, correct, and appropriate rules of state administrative law and their effective implementation to guarantee the legal protection of holders of land rights certificates. Second, in instances where land is required for the implementation of public development, the acquisition process must be conducted expeditiously and in a transparent manner, while maintaining due consideration for the protection of legitimate rights to land. The legal basis for land acquisition for the implementation of development in the public interest as stipulated by Presidential Decree No. 55 of 1993 is no longer deemed appropriate in the current legal landscape. The issuance of Presidential Regulation No. 36 of 2005, which has been amended by Presidential Regulation No. 65 of 2006, is founded on several legal instruments. This research leads to the conclusion that the government's objective is to provide a form of protection and guarantee of legal certainty over land ownership for individuals. This is achieved through the registration of land rights as outlined in Article 19, Paragraph 1 of Law Number 5 of 1960 concerning Basic Agrarian Regulations. The form of legal protection for people's rights to land in development is to provide legal protection for holders of land rights to their land